Mobile apps for orthopedic surgeons: how useful are they? - Franko OI (Orthopedic Research and Reviews, 2015)
Orrin I Franko,1 John P Andrawis,2 Dayne T Mickelson31Department of Orthopedic Surgery, University of California, San Diego Medical Center, San Diego, CA, USA; 2Department of Orthopedic Surgery, Harbor-University of California, Los Angeles Medical Center, Torrance, CA, USA; 3Department of Orthopedic Surgery and Sports Medicine, University of Washington, Seattle, WA, USAAbstract: Smartphone apps have become an integral part of medical training and practice in the hospital and clinical setting. However, to ensure the safety of patient care, it remains imperative that physicians and physician-educators alike continue to monitor and recognize the strengths and limitations of these powerful tools. Orthopaedic surgeons have widely adopted the use of smartphones and tablets and consequently, a number of resources have emerged to assist orthopaedic trainees and providers in discovering and assessing the most appropriate apps for their practice. The purpose of this review article is to advise readers on how best to identify apps for orthopaedic surgeons, summarize the most popular and useful existing apps, present the current available data to support their use, and provide recommendations to the orthopaedic community regarding safe and responsible mobile technology use in clinical practice.Keywords: smartphone, tablet, mobile, apps